2014
DOI: 10.1111/dth.12188
|View full text |Cite
|
Sign up to set email alerts
|

Ingenol mebutate gel treatment for actinic cheilitis: report of four cases

Abstract: Actinic cheilitis (AC) are premalignant lesions that have an increased risk of malignant transformation. Their treatment, therefore, is essential to prevent carcinogenesis. However, optimal therapy is not well established and different modalities yield variable results. Ingenol mebutate gel has recently been approved by the US Food and Drug Administration for topical treatment of actinic keratosis, with high clearance rates. On the basis of these findings, we report our experience with this drug for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…To our knowledge, only Barrado-Sol ıs et al (14) have previously reported four cases of AC treated with IM with variable results (14). We consider this option as a valid alternative with need of further study.…”
Section: Discussionmentioning
confidence: 83%
“…To our knowledge, only Barrado-Sol ıs et al (14) have previously reported four cases of AC treated with IM with variable results (14). We consider this option as a valid alternative with need of further study.…”
Section: Discussionmentioning
confidence: 83%
“…Treatments have been used for the treatment of actinic cheilitis, as shown in Table 3 (Robinson 1989;Dufresne et al 2008;Lima Gda et al 2010;Shah et al 2010;Ulrich et al 2011; Jadotte and Schwartz 2012b; Barrado Solís et al 2015).…”
Section: Basic Conceptsmentioning
confidence: 99%
“…There is no agreement on the frequency in which actinic cheilitis (AC) becomes squamous cell carcinoma (SCC), but SCC of the lip is a highrisk body site for metastatic progression (11% vs. 1% in other locations) and recurrences (Barrado Solís et al, 2015;Benati, Persechino, & Piana, 2017). Thus, it is crucial to treat AC adequately.…”
Section: Introductionmentioning
confidence: 99%
“…Local skin response (LSR) score include erythema, flaking or scaling, crusting, swelling, vesciculation, pustulation, and erosion or ulceration (Rosen, Marmur, Anderson, Welburn, & Katsamas, 2014). Few case series examined the effectiveness of IngMeb for the treatment of AC using clinical and dermoscopy examination (Barrado Solís et al, 2015;Fl orez, Batalla, & De La Torre, 2017;Tzika, Masouy e, M€ uhlstädt, & Laffitte, 2016). Dermoscopy and reflectance confocal microscopy (RCM) are currently the most used noninvasive imaging techniques that help clinicians not only to achieve high diagnostic accuracy for skin cancer diagnosis but also to monitor treatments over time (Fargnoli, Kostaki, & Piccioni, 2012;Longo et al, 2012;Maher et al, 2016).…”
Section: Introductionmentioning
confidence: 99%